Identity construction in the UK higher education: How cultural gendered identity is shaped through leadership practice - Tanya Linaker (Peoples' Friendship University of Russia (RUDN University), 2023)
This article is a case study of the cultural gendered professional identity construction of an educational leader contextualised by an ethnically diverse and multilingual UK University language centre. The leadership identity of the female participant is co-constructed by the researcher through narrative-in-interaction to reveal its dilemmatic nature, being agentive and influenced by external forces and being unique vis-a-vis belonging to the wider community, staying the same and being subject to change. The study is presented within a Post Structuralist framework and views discourse as a means of identity construction. The implicit and explicit identity claims are elicited through small story analysis at three levels of positioning - against story actors, against the interlocutor and in relation to global discourses to ensure the best scrutiny of multiple and contradictory identity claims. The article gives voice to the underrepresented ethnic minority of female educational leaders by revealing boundaries to leadership identity development against discourses of gender ideology, marriage, ethnicity, migration, illness, death, work/life balance, professional success, and leadership learning. It also aims to contribute to the body of research on small story and positioning analysis.